Epigenetics of cancer prevention - Bishayee, Anupam; Bhatia, Deepak (Translational epigenetics series, 2019)
Epigenetics of Cancer Prevention, Volume Ten is the first to look at epigenetics and chemoprevention together. Although there is numerous scientific data available on how epigenetics can lead to cancer and how chemoprevention can be beneficial in the treatment of, or improvement of quality of life, together they will set an advanced understanding for the reader in this upcoming field of chemoprevention influencing epigenetics. This book discusses molecular epigenetic targets of natural products, such as green tea polyphenols, curcumin and resveratrol, and organ specific epigenetic targets related to diverse types of cancer, for example prostate, colorectal, breast, lung and skin cancers. Additionally, it encompasses a discussion on research methods and limitations to study epigenetics and epigenomics of chemopreventive drugs and personalized cancer treatment with phytochemicals. The book is ideal for cancer researchers, health care professionals and all individuals who are interested in cancer prevention research and its clinical applications, especially in natural remedies.